The echo of “no”: how negating language silences the mind of the future innovative physician. - Peñaloza-Morales, Albert José (Spanish Journal of Medical Education, 2026)
Language used in clinical teaching plays a central role in how students and residents construct their learning, motivation, and relationship with error. From the perspective of training in Emergency Medicine, this article reflects on the repeated use of negation, expressed through a categorical “no”, as a common corrective mechanism in clinical teaching environments, and on how this form of interaction may affect psychological safety, willingness to participate, and cognitive processes in learners. Drawing on insights from medical education, the neuroscience of learning, and emotional intelligence, it examines the emotional, ethical, and pedagogical implications of this type of language, as well as the cultural and hierarchical factors that contribute to its persistence. Finally, it argues for a shift toward more orienting and reflective forms of feedback that preserve academic rigor without relying on fear, promoting learning environments that are safer and more conducive to critical thinking and innovation.